Evaluation of the corneal epithelium of rabbits treated with preservative-free eye drops containing ketorolac tromethamine or diclofenac sodium - Pereira , Fabiana Quartiero (2023)
This study aimed to evaluate the corneal epitheliotoxic effects of preservative-free ketorolac tromethamine 0.5% and diclofenac sodium 0.1% eye drops in rabbits. Seventeen New Zealand rabbits were randomly divided into three groups: the 0.5% ketorolac tromethamine group, the 0.1% diclofenac sodium group, and the control group (0.9% NaCl). For each rabbit, both eyes were treated three times daily according to their treatment group. The corneal epithelia were analyzed using scanning electron microscopy to observe the number of light, grey, and dark cells; the number of epithelial holes; and the loss of hexagonal shape. Both of the formulations administered caused changes in the healthy corneal epithelia of rabbits. Except for number of epithelial holes (p < 0.05), all the parameters showed a statistically significant difference between the groups. The number of dark cells was highest in the ketorolac tromethamine group (p<0.05). The number of grey cells was higher in the diclofenac sodium group than in the control group (p =0.003). A higher number of dark cells was associated with a smaller number of light cells (r =-0.577, p < 0.001). Loss of shape showed a direct correlation with the number of dark cells (r=0.524, p=0.002). Based on the results presented, it was possible to conclude that ketorolac tromethamine 0.5% was more toxic to rabbit corneal epithelium than diclofenac sodium 0.1%. Keywords: cornea; nonsteroidal anti-inflammatory agent; ophthalmic solutions; scanning electron microscopy